Utilization of innovative medical technologies in German inpatient care: does evidence matter? - Helene Eckhardt; Susanne Felgner; Marie Dreger; Sabine Fuchs; Hanna Ermann; Hendrikje Rödiger; Tanja Rombey; Reinhard Busse; Cornelia Henschke; Dimitra Panteli (BMC, 2023)
Abstract Background The reimbursement of new technologies in inpatient care is not always linked to a requirement for evidence-based evaluation of patient benefit. In Germany, every new technology approved for market was until recently eligible for reimbursement in inpatient care unless explicitly excluded. The aim of this work was (1) to investigate the type of evidence that was available at the time of introduction of 25 innovative technologies and how this evidence evolved over time, and (2) to explore the relationship between clinical evidence and utilization for these technologies in German inpatient care. Methods This study combined different methods. A systematic search for evidence published between 2003 and 2017 was conducted in four bibliographic databases, clinical trial registries, resources for clinical guidelines, and health technology assessment-databases. Information was also collected on funding mechanisms and safety notices. Utilization was measured by hospital procedures captured in claims data. The body of evidence, funding and safety notices per technology were analyzed descriptively. The relationship between utilization and evidence was explored empirically using a multilevel regression analysis. Results The number of included publications per technology ranges from two to 498. For all technologies, non-comparative studies form the bulk of the evidence. The number of randomized controlled clinical trials per technology ranges from zero to 19. Some technologies were utilized for several years without an adequate evidence base. A relationship between evidence and utilization could be shown for several but not all technologies. Conclusions This study reveals a mixed picture regarding the evidence available for new technologies, and the relationship between the development of evidence and the use of technologies over time. Although the influence of funding and safety notices requires further investigation, these results re-emphasize the need for strengthening market approval standards and HTA pathways as well as approaches such as coverage with evidence development.